Dynamic production, storage, and use of renewable hydrogen: A technical-economic-environmental analysis in the public transport system in São Paulo state, Brazil - Moura, Carlos Henrique Silva [UNESP]; Silveira, José Luz [UNESP]; Lamas, Wendell de Queiróz (Elsevier, 2020)
This article proposes a calculation methodology that starts from the demand calculation to supply a fleet bus with renewable hydrogen based on the electrolysis process until the energetic, economic, and environmental analyses, involving all the processes of the productive chair. Also considering the dynamic behaviour of the following hydrogen processes: production, storage, and use. The simplified scheme of the proposed system configuration to be studied consists of the use of alternative and renewable sources of energy (solar-wind-biogas) to generate electrical energy in order to produce hydrogen from electrolysis of the water, which is stored in its gaseous state and subsequently redirected to a filling station to be used as vehicle fuel in buses. The results show that to feed one bus the hybrid system generates an average of 78,110 kWh/month with an installed capacity of 1101.905 kW, producing 1209.90 kgH2/month through the electrolysis process from water. The results also show a range of electricity generation costs between 1.130 and 0.123 US$/kWh and H2 production between 0.963 and 0.110 US$/kWh. Concluding that the application of renewable energies to produce hydrogen and electricity for the public transport sector is an attractive alternative in the future throughout the country, because the proposed system is technically, economically and ecologically viable.
Keywords: Bioenergy; Hybrid system; Public transportation; Solar energy; Vehicular hydrogen; Wind energy